The development of photoredox-mediated methods for the aminofunctionalisation of alkenes - Dhak, Mandeep Singh (2023)
Nitrogen-centered radicals (NCRs), such as amidyl radicals, are a versatile reaction intermediate for the installation of C–N bonds by means of the functionalisation of alkenes. In this thesis, the development of photoredox-mediated methodologies for the aminofunctionalisation of alkenes by means of reductively generated amidyl radicals is described, and its application towards the synthesis of amino-substituted all-carbon quaternary centres and saturated heterocycles. We disclose an efficient method for the synthesis of β-aminoketones containing all-carbon quaternary centres in a photoredox-mediated one-pot procedure utilizing semi-pinacol chemistry and reductively generated amidyl radical, achieving yields of up to 96%. Good functional group tolerance is observed in a variety of positions around the aryl ring. Application of this chemistry has also been demonstrated on unactivated alkene substrates and acylic substrates, which to the best of our knowledge has not been demonstrated in the literature using photoredox-based methodology. In addition, we also disclose a robust method for the synthesis aminomethyl-substituted tetrahydrofurans, utilizing a photoredox-based radical-polar crossover methodology and reductively generated amidyl radicals. This chemistry has been demonstrated to attain yields of up to 82%, and be compatible to the synthesis of other saturated heterocycles such as pyrrodilines, morpholines and lactones.